2021
DOI: 10.3390/coatings11030273
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Shear Bond Strength of Flowable Self-Adhering Resin-Composites Adhesive to Dentin with a Conventional Adhesive

Abstract: This study aimed to measure and compare the shear bond strength (SBS) of a self-adhering flowable resin composite to dentin with a conventional flowable composite, and evaluate the various modes of failure. Thirty human premolar teeth (n = 30) were randomly allocated to two groups (Group I: Vertise™ Flow; Group II: Filtek Ultimate + Single Bond Universal) of 15 specimens each, and SBS was measured for specimens from each group by applying a shear load using a universal testing machine (UTM). Modes of failure w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Ceramic nanoparticles such as TiO 2 and ZrO 2 NPs are primarily used for this purpose [6,7]. TiO 2 NPs are white solids and considered technologically crucial due to their various properties [8,9] such as ease of synthesis, good tensile strength [10,11] adequate biocompatibility [12], antibacterial activity [13], and photocatalytic activity [11]. TiO 2 NPs are widely used as catalyst supports in biomedicine, water and air purification [14], pigments [14], cosmetics, solar cells [15], and tissue engineering [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Ceramic nanoparticles such as TiO 2 and ZrO 2 NPs are primarily used for this purpose [6,7]. TiO 2 NPs are white solids and considered technologically crucial due to their various properties [8,9] such as ease of synthesis, good tensile strength [10,11] adequate biocompatibility [12], antibacterial activity [13], and photocatalytic activity [11]. TiO 2 NPs are widely used as catalyst supports in biomedicine, water and air purification [14], pigments [14], cosmetics, solar cells [15], and tissue engineering [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The failure modes were examined under a stereomicroscope with magnification, and they were categorized as follows: adhesive (A; failure at the repair-substrate-bonded interfaces), cohesive (C; failure at least parts of the substrate or the repair composite), or mixed (M; A + C). 17…”
Section: Microshear Bond Strength Testingmentioning
confidence: 99%
“…Therefore, they involve fewer application steps, reduced chair time, and a minimum risk of handling mistakes. 17 SARCs can be used for the restoration of small occlusal cavities or noncarious cervical lesions; alternatively, they can be used as a liner under definitive restorative material. 18 As a result of their favorable properties, SARCs can also be used as intermediate materials in VPT.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the step of applying dental adhesive between the prepared dental surface and dental composite can be eliminated. Asiri et al [ 72 ] compared the shear bond strength of flowable composite with dentin and a conventional adhesive, and they found that the flowable composite has lower shear bond strength compared to a conventional adhesive-restored dentin. David et al [ 73 ] found that the adhesive strength of self-adhesive flowable composite to dentin and enamel is lower than that of conventional bonding with composite resins and self-etching adhesives.…”
Section: Dental Filling Compositementioning
confidence: 99%